Analisis Kepuasan Pelanggan Restoran Mie Gacoan Galuh Mas Karawang Menggunakan Importance Performance Analysis (IPA) Matrix - Rofrilia Riestiana; Ina Ratnasari (Journal of Management and Creative Business, 2026)
The competitive culinary industry demands that restaurants provide service quality that meets customer expectations. This study aims to analyze the level of service importance and performance, measure customer satisfaction, identify attributes that are priority for improvement using Importance–Performance Analysis (IPA), and provide recommendations for Mie Gacoan Karawang. The study used a quantitative approach with the IPA method. Data were collected through a questionnaire using Google Forms from 200 respondents selected using a purposive sampling technique. Analysis was conducted by calculating the average importance and performance scores, gap values, differentiating test, and mapping attributes into an IPA Cartesian diagram. The results of the study indicate a significant difference between the level of importance and the level of performance, so that service quality does not fully meet customer expectations. The results of the IPA mapping indicate that facility cleanliness, timely serving, and service quality are the main priorities for improvement, while food quality, order conformity, dining experience, convenience of location, and suitability of quality to price need to be maintained. The results of this study are expected to provide a basis for management in improving service quality and customer satisfaction.